Structural and Semantic Features and Ways of Translation of Military Discourse Terminology (on Material of English Periodicals) - K. A. Degtyarenko (Научный диалог)
The most productive ways of formation of modern terminology of military discourse - multicomponent combinations - are covered. Appeal to the study of military terminology is relevant due to its intensive development in conditions of modern technological progress. The basic structural formulas of multicomponent terminological combinations and most productive nuclear terms are revealed, on the basis of which the multicomponent terminological groups are formed. There are two diametrically opposite tendencies in the formation of multicomponent terminological combinations of the military discourse. One of them consists in minimizing the nomination due to adhesions or removing components of attribute group. Another trend is the progressive complication of the object nomination by adding the specific characteristics of the core. It is proved that the increase in the length of terminological combination increases its semantic capacity, but at the same time leads to the weakening of cross-media semantic valence. The impact of these terminological characteristics on features and correctness of the translation is evaluated. It is emphasized that the translator is faced with the need of elaborating a strategy in the translation of the term. The analysis showed that the main methods of translation of the terminological combinations are calques and descriptive translations and transcription / transliteration - the techniques that are used to translate single-word terms in the composition of the multicomponent combinations.